Alpha Female dalam Membentuk Pola Asuh Anak di Kota Bandung - Khoirunnisa, Syifa; Ruyadi, Yadi; Utami, Nindita Fajria (Pusat Studi Wanita dan Keluarga UGM, 2024)
The role of parents as leaders in the dynamics of families in Kota Bandung is increasingly complex, given the significant influence they have on the upbringing patterns of children. Critical questions arise regarding the impact of a working mother on the development of a child, sparking debates on whether the loss of this role has a significant effect or not. This research aims to determine the influence of Alpha Female on parenting patterns in the city of Bandung. The method used is a quantitative approach, with a population of 100 children aged 17-25 years in the areas of North Bandung, East Bandung, West Bandung and South Bandung. This research focuses on the relationship between Alpha Female and parenting patterns in Bandung City. The results of data analysis show that there is a significant positive correlation between the Alpha Female variable and parenting patterns, with a correlation coefficient value of 0.198. The coefficient of determination of 19% implies that most of the variation in parenting patterns can be explained by the role of the Alpha Female, while the remaining 81% is influenced by other factors not discussed in this study. Simple linear regression analysis confirms that Alpha Female has a significant influence on parenting patterns, with a t-test significance value of 0.048. Rejection of H0 and acceptance of Ha is supported by tcount (2.004) which exceeds the ttable value at the significance level of 0.05. These results provide a strong indication that the role of Alpha Female has a significant impact in shaping child rearing patterns in the city of Bandung. Thus, this research offers an important contribution in understanding the dynamics of the relationship between Alpha Females and parenting patterns.